(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
The article discusses various modern methods of creative pedagogy designed to enhance student learning and prepare them for the complexities of the future. It highlights seven innovative approaches: Project-Based Learning (PBL), STEAM Education, Flipped Classroom, Gamification, Maker Education, Inquiry-Based Learning (IBL), and Collaborative Learning.